Expanding access to group singing for people with dementia: implications of music therapy skill sharing for research and practice - Dowson, Elizabeth Rebecca Mary (2020)
Background: 850,000 people in the UK are estimated to be living with dementia. The importance of supporting people with dementia and their carers through psychosocial interventions is widely acknowledged. The potential of music-based interventions to provide this support is becoming well-recognised, but demand exceeds supply. Group singing is an increasingly popular activity for people with dementia and their carers, and a growing number of community based singing groups are being implemented. However, to date there have been no large-scale studies demonstrating the benefits of community group singing for this population. Music therapy skill-sharing is a way of supporting facilitators without formal therapy training, and increasing capacity to provide singing opportunities, but we need to know how these skills can be communicated most effectively and efficiently. The CHORD (Chorus Research in Dementia) manual has been developed by music therapists to provide guidance to singing group facilitators.